Hybrid Control DC Microgrid Embedded With BESS and Multimode Adaptive Standalone PV - Akanksha Shukla; Mohammed Imran; Kusum Verma; Hitesh R. Jariwala (International Transactions on Electrical Energy Systems)
The advantages of DC distribution over AC distribution, combined with greater penetration of photovoltaic (PV) systems, have enhanced the popularity of DC microgrids. With the intermittency of a PV system, power management in a DC microgrid is an issue, but it can be addressed by using a battery energy storage system (BESS) as a backup. The goal is to maintain a constant DC-link voltage while balancing demand and supply. The study establishes a hybrid control approach for a DC microgrid involving PV, BESS, and DC loads, utilizing both the PV system and the BESS. PV will operate as a primary voltage regulator, making BESS a secondary control, resulting in decreased battery consumption and extended battery life. To achieve this objective, a flexible power point tracking (FPPT) algorithm is suggested, which requires the PV to track the load profile by adaptively modifying its PV power output. The effectiveness of the devised control method is tested by running time domain simulations on several case studies. To assess the adapted system’s tolerance to seasonal changes, k-means clustering is utilized to generate a cluster of irradiance profiles. These clustering solar irradiance and load profiles were simulated for 24 h to illustrate the resilience of the devised control method.